Employment of Silicon Nitride Films Prepared by DC Reactive Sputtering Technique for Ion Release Applications - Taher, Diyar Ali; Hameed, Mohammed Abdullah (Iraqi Journal of Physics, 2023)
In this work, silicon nitride (Si3N4) thin films were deposited on metallic substrates (aluminium and titanium sheets) by the DC reactive sputtering technique using two different silicon targets (n-type and p-type Si wafers) as well as two Ar:N2 gas mixing ratios (50:50 and 70:30). The electrical conductivity of the metallic (aluminium and titanium) substrates was measured before and after the deposition of silicon nitride thin films on both surfaces of the substrates. The results obtained from this work showed that the deposited films, in general, reduced the electrical conductivity of the substrates, and the thin films prepared from n-type silicon targets using a 50:50 mixing ratio and deposited on both surfaces of a titanium substrate reduced the electrical conductivity of this substrate by 30%. This reduction in the release of ions from the coated metal substrate is attributed to the dielectric properties of the deposited silicon nitride thin films. This result is very important and applicable. This work represents the first attempt in Iraq to study such effects and may represent a good starting point for advanced studies in biomedical engineering.